An assessment on the quality of abstracts presented at the British Association of Urological Surgeons annual meeting. (September 2014) - Jones, JET; Lam, JHP; Stewart, GD; McNeill, SA; Laird, A
Objectives: To assess the quality of abstracts presented at the British Association of Urological Surgeons (BAUS) annual meeting using standardized reporting guidelines and examine whether abstract quality is associated with conversion to full-text publication. Materials and methods: Two standardized assessment forms based on CONSORT/STROBE guidelines were used to score abstracts from the 2009 BAUS meeting retrospectively. A high score ratio was defined as >50% of criteria. Kaplan–Meier analysis examined effect of score ratio on time to publication; logistic regression examined predictive potential of variables including; session topic, study design, country of origin and number of institutions to high score ratio and the effects the above factors and a high score ratio on the likelihood of full-text publication. Results: In total, 127 abstracts were included. The mean score ratio was 63.6% (SD 13.3%) for observational studies and 62.7% (SD 9.5%) for randomized controlled trials (RCTs). Nine RCT abstracts and 91 non-RCT abstracts achieved a high score ratio. Abstract topic, study design, country of origin and number of institutions did not predict a high score ratio or subsequent full-length publication using multivariate logistic regression. Full-length publication was achieved for 43 (33.9%) abstracts. Mean time to publication was 17.2 months. Abstract quality did not predict time to publication ( p =0.706). Conclusion: BAUS abstracts are of high quality, and compare favourably with other urological meetings. While abstract quality does not independently predict full-length publication, most abstracts do not progress to full-length publication and thus we advocate the use of standardized reporting guidelines to ensure accurate interpretation of study methodology and results.